TITAH RAJA KASULTANAN YOGYAKARTA DALAM PERSPEKTIF TEORI BESLISSINGENLEER TER HAAR - Sekhar Chandra Pawana (Justitia et Pax, 2020)
This paper discusses on the theoretical perspective of Beslissingenleer Ter Haar on decree of the king of Kraton Ngayogyakarta Hadiningrat. The issue of this paper is how the perspective of Ter Haar’s beslissingenleer theory on decree of the king of Kraton Ngayogyakarta Hadiningrat as the functionary of adat law. This paper was conducted under the basis of normative method with statute approach, as secondary data were obtained from the literature related with the topic. The existence of decree of the king is a form of the exixtence of legal functionaries that can make a law in the fellowship of adat law, especially the Kraton Kasultanan of Yogyakarta.